2006
DOI: 10.1007/s11274-005-9051-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Production of Isochainin by a Strain of Streptomyces sp. Isolated from Rhizosphere Soil of the Indigenous Moroccan Plant Argania Spinosa L

Abstract: An actinomycete strain (designated Ap1) isolated from the rhizosphere soil of Argania spinosa L. strongly inhibited the growth of two plant pathogens: Fusarium oxysporum f.sp. albedinis and Verticillium dahliae. The spore morphology suggested that the Ap1 strain belonged to the genus Streptomyces. The antifungal compound produced by Ap1 was purified by HPLC and identified as the polyene macrolide, isochainin, by NMR and mass spectroscopy. Ap1 showed normal biosynthesis of isochainin in comparison with S. cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…In this paper, strain Ap1 T , with antagonistic activity towards some phytopathogens (Bouizgarne et al, 2006), was shown to present a colonial morphology and cell-wall chemistry consistent with its assignment to the genus Streptomyces. In the present investigation, strain Ap1…”
supporting
confidence: 62%
See 1 more Smart Citation
“…In this paper, strain Ap1 T , with antagonistic activity towards some phytopathogens (Bouizgarne et al, 2006), was shown to present a colonial morphology and cell-wall chemistry consistent with its assignment to the genus Streptomyces. In the present investigation, strain Ap1…”
supporting
confidence: 62%
“…T was isolated from a soil sample collected from the rhizosphere of an argan tree (Argania spinosa L.) as described by Bouizgarne et al (2006). The isolate was grown on oatmeal agar [International Streptomyces Project (ISP) medium 3; Kuster, 1959] at 28 u C for 2 weeks and stored at room temperature.…”
Section: Strain Ap1mentioning
confidence: 99%
“…on plant pathogens, for example: S. rochei on Phytopthora root rot of pepper (Ezziyyani et al 2007); S. griseoviridis on Fusarium root rot and wilt of tomato (Minuto et al 2006); S. platensis on R. solani leaf blight/seedling blight of rice (Wan et al 2008); S. hygroscopicus on Colletotrichum gloeosprioides anthacnose of several crops (Prapagdee et al 2008 the ability of Streptomyces to produce antifungal and antibacterial substances was supported by many reports and the Streptomyces are also a major source of innumerable antibiotic agents (Mahadevan and Crawford 1997;Neeno et al 2001;Lee and Hwang 2002). The success attained by using Streptomyces as a biocontrol agent of plant diseases has been reported in studies such as Bouizgarne et al (2006) who found that the Streptomyces sp. Ap1 produced isochainin and strongly inhibited the growth of two pathogens Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 98%
“…Another characteristic of Actinomycetes that lead to such an impact on variation in composition is the ability of a good deal of them to produce antimicrobial compounds, thus allowing them to impact the community around them [59][60][61][62]. Actinomycetes have also been described as increasing in abundance in subsurface [63], which gives validity to the observation of the constantly eroded soil surface of the TSS, possibly allowing subsurface microbiota to become predominant in such an environment.…”
Section: Clustering Of Samples According To Community Structurementioning
confidence: 99%